BUYER-SUPPLIER COLLABORATION AND SUPPLY CHAIN RESILIENCE: A CASE STUDY IN THE PETROCHEMICAL INDUSTRY - Botes, Antonie; Niemann, Wesley; Kotzé, Theuns (The South African Journal of Industrial Engineering, 2017)
The purpose of this study was to investigate the underlying mechanisms through which buyer-supplier collaboration enables resilience. A single case study method was adopted, examining a critical case within the petrochemical industry. Data was collected through semi-structured interviews. The rationale for undertaking buyer-supplier collaboration in the focal firm is grounded in Kraljic’s procurement matrix, accounting for underlying risks of supply disruptions that are inherent in the resilience discourse. The findings suggested that collaboration between buyers and suppliers does not directly lead to supply chain resilience, but rather enables the antecedents to supply chain resilience. The study developed an understanding of the specific mechanisms through which the antecedents of resilience are enabled in the petrochemical industry.